Site occupancy of select mammals in the tropical forest of Eastern Himalaya - Ahmad, Arif; Gopi, Govindan Veeraswami (Frontiers in Ecology and Evolution, 2024)
Introduction Terrestrial mammals play a pivotal role in tropical forest ecosystems, representing a rich and functionally diverse component of these biomes. However, they confront formidable threats globally, such as hunting, habitat loss, and fragmentation, amidst the expansion of human-altered landscapes in tropical regions. Understanding the impacts of these changes on mammal communities is crucial for designing effective conservation interventions. Northeast India's tropical forests, a biodiversity hotspot, host a diverse array of mammalian fauna. The primary challenge faced by these species involves anthropogenic activities leading to the shrinkage and fragmentation of forested habitats. Methodology In this study, we conducted systematic camera trapping in Mehao Wildlife Sanctuary (WLS) to assess mammal status and distribution. Employing single-season occupancy models, we evaluated factors influencing mammalian species' detection probability and spatial utilization within the landscape. Results The study documented 27 mammalian species, with 12 identified as "threatened" on the IUCN Red List. Species like clouded leopard, marbled cat, Gongshan muntjac, red goral, Mishmi takin, and sambar were recorded but observed infrequently. Notably, we reported the Asiatic brush-tailed porcupine's first sighting in Mehao. Our findings revealed that undisturbed forest habitats were preferred by all species. Mainland serow dominated most of the sanctuary's area, followed by northern red muntjac, yellow-throated marten, and masked palm civet. Discussion The response of mammalian species to ecological and anthropogenic covariates varied significantly, underscoring the necessity for species-specific management strategies alongside a landscape-scale conservation approach. These outcomes emphasize the urgency of managing and safeguarding rare and elusive mammalian species within and around Mehao WLS.